Impact of Prasugrel and Ticagrelor on Platelet Reactivity in Patients With Acute Coronary Syndrome: A Meta-Analysis - Dai, Lulu; Xu, Jiawei; Jiang, Yuerong; Chen, Keji (Frontiers in Cardiovascular Medicine, 2022)
Background: This meta-analysis mainly aimed to compare the impact of prasugrel and ticagrelor on PR in patients with ACS. Methods: We searched four electronic databases to identify randomized controlled trials and cohort studies comparing the impact of prasugrel and ticagrelor on PR in patients with ACS. We performed group analyses according to three detection methods, drug dose and LD effect time. Results: Twenty-five studies with 5098 patients were eligible. After LD, the incidence of HTPR of ticagrelor was significantly lower than that of prasugrel within 6-18 hours based on VASP test, there was no significant difference between ticagrelor and prasugrel in the following results: platelets inhibitory effect within 24-48 hours based on VN assay and VASP test, and the incidence of HTPR within 2-6 hours based on VN assay and within 24-48 hours based on VN assay and VASP test, the incidence of LTPR within 6-18 hours based on VASP test and 48 hours based on VN assay and VASP test. After MTD, the platelet inhibitory effect of ticagrelor was stronger than that of prasugrel based on VN assay and VASP test, the incidence of HTPR of ticagrelor was significantly lower than that of prasugrel based on VN assay, the incidence of LTPR of ticagrelor was significantly higher than prasugrel based on VN assay and VASP test, the results of MEA test were inconsistent with the other two methods. There was no significant difference between ticagrelor and prasugrel in thrombosis/ischemic events, TIMI major bleeding and bleeding BARC type ≥ 2. The risk of bleeding BARC type 1 of ticagrelor was significantly higher than prasugrel. Conclusions: Compared with prasugrel, ticagrelor might have a stronger platelet inhibition effect, with a lower incidence of HTPR and a higher incidence of LTPR and bleeding BARC type 1, while there might be no significant difference in the risk of thrombosis/ischemic, bleeding BARC Type ≥ 2 and TIMI major bleeding. A higher incidence of LTPR might indicate a higher risk of bleeding BARC type 1. The results of VN assay were consistent with that of VASP test, and not with the MEA test.